The role of corporate social responsibility in modern economic theory and activities of multinational enterprises - E. L. Pavlov (Вестник университета)
The purpose of the article is to consider the place of corporate social responsibility in modern economic theory. The materials devoted to the concept of corporate social responsibility have been analyzed. It has been concluded, that today the arguments in favor of corporate social responsibility are more convincing than the arguments of opponents of this concept. The direction of further priority development of the concept in the direction of greater practical value has been specified and the necessity to strengthen research related to the interdependence of employee motivation and corporate social responsibility has been indicated.